Friction material

By using inorganic particles and titanates of specific particle sizes and hardness in the friction material, the problems of uneven transfer films and brake vibration in the prior art are solved, and high wear characteristics and stable friction properties are achieved.

CN119546721APending Publication Date: 2025-02-28AKEBONO BRAKE IND CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380052167.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-07-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to uniformly form a moderate transfer film, resulting in unstable friction coefficient and uneven wear, and brake vibration is easily caused during high-temperature braking.

Method used

The friction material without copper components is made by inorganic particles containing specific particle sizes and hardness, but inorganic particles containing specific particle sizes and hardness, and titanate salts with specific particle sizes.

Benefits of technology

It is achieved that the transfer film is appropriately formed without the copper component, suppressing brake vibration, and improving wear characteristics of the friction material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229893370000141
    Figure BDA0005229893370000141
Patent Text Reader

Abstract

The present invention relates to a friction material containing a friction adjusting material, a binding material, and a fiber base material, the friction material not containing inorganic particles having an average particle diameter of 3 [mu] m or less and a Mohs hardness of 6 or more, but containing inorganic particles having an average particle diameter of 15 [mu] m to 60 [mu] m and a Mohs hardness of 6 or more, and containing a titanate having an average particle diameter of 20 [mu] m or more, and does not contain a copper component.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a friction material for brake pads, brake linings, clutch friction plates and the like used in automobiles, railway vehicles, industrial machinery and the like. Background Art

[0002] Friction materials used in brakes such as disc brakes and drum brakes, or clutches, etc. are composed of raw materials such as a fiber base material that plays a reinforcing role, a friction adjusting material that plays a friction role and adjusts its friction performance, and a binder that integrates these components.

[0003] In the past, materials containing copper components such as copper fibers and copper powder were used for various purposes. For example, the copper component has high ductility and malleability, so when the friction material and the counterpart material (disc rotor) are braked, the components of the friction material composition are easily transferred to the surface of the counterpart material to form a transfer film (transfer film). By making the transfer film function as a protective film, the friction coefficient can be maintained and the wear of the counterpart material can be suppressed. In this way, from the perspective of improving the characteristics of the brake, it is important to control the formation of the transfer film.

[0004] However, in recent years, from the viewpoints of environmental pollution problems and harmfulness to human body, a friction material containing substantially no copper component has been desired.

[0005] As friction material components that participate in the formation of the transfer film, various organic substances, titanates, etc. are known. Here, in the friction material described in Patent Document 1, it is described that by using plate-like titanates and hydrous magnesium silicate at the same time, the transfer film can be controlled to a suitable thickness. In addition, in the friction material described in Patent Document 2, it is described that during light load braking at low speed, a good transfer film is formed by the decomposition product of the organic filler and the extension product of the titanate.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2012-197352

[0009] Patent Document 2: Japanese Patent Application Publication No. 2017-2186 Summary of the invention

[0010] Technical problem that the invention aims to solve

[0011] However, the purpose of the friction materials described in Patent Documents 1 and 2 is to increase the transfer film on the surface of the counterpart material in order to compensate for the effect of copper, but there is no description of uniformly forming the transfer film. On the other hand, if the transfer film is excessively limited, the stabilization of the friction coefficient and the suppression of wear are impaired, so it is desired to obtain a friction material that forms a uniform and appropriate transfer film.

[0012] In addition, during high-temperature braking, there is a problem that brake vibration is easily generated due to the uneven temperature rise on the surface of the object material. As a cause of brake vibration, there is a concern that the surface pressure of the friction material will increase locally due to the vibration of the disc rotor, and the transfer and adhesion friction to the surface of the object material will become uneven. The portion where the transfer and adhesion friction to the surface of the object material increases will increase in temperature, causing the surface of the object material to thermally expand unevenly, thereby generating a wall thickness difference on the surface of the object material. Due to the wall thickness difference on the surface of the object material, the contact between the friction material and the object material becomes uneven, which may become a cause of brake vibration.

[0013] Therefore, an object of the present invention is to provide a friction material which can appropriately form a transfer film and suppress the vibration generated in the brake even if the friction material does not substantially contain a copper component.

[0014] Technical solutions to the problem

[0015] The present inventors have found that the above-mentioned problems can be solved by not containing inorganic particles having a specific particle size and a specific hardness, but containing inorganic particles having a specific particle size and a specific hardness and containing titanate having a specific particle size.

[0016] That is, the present invention is as follows.

[0017] [1] A friction material comprising a friction adjusting material, a bonding material and a fiber substrate, wherein:

[0018] The friction material does not contain inorganic particles with an average particle size of 3 μm or less and a Mohs hardness of 6 or more.

[0019] The friction material contains inorganic particles with an average particle size of 15 μm to 60 μm and a Mohs hardness of 6 or more.

[0020] The friction material contains titanate having an average particle size of 20 μm or more and does not contain a copper component.

[0021] Effects of the Invention

[0022] According to the present invention, the transfer degree of the transfer film formed based on the titanate can be controlled by using a titanate having a large average particle size instead of a transfer film formed based on the copper component. Furthermore, inorganic particles with a small average particle size that are easy to enter the transfer film are not contained, but inorganic particles with a large average particle size are contained as grinding materials, so that local transfer on the surface of the object material can be suppressed. Therefore, even if the copper component is not substantially contained, the transfer film can be appropriately formed, and a friction material with high wear characteristics can be obtained. DETAILED DESCRIPTION

[0023] Hereinafter, the present invention will be described in detail, but these are merely examples of preferred embodiments, and the present invention is not limited to these contents.

[0024] The friction material of the present invention does not contain copper components. It should be noted that "does not contain copper components" means that copper components are substantially not contained as an effective component for realizing functions such as wear resistance, and does not mean that copper components such as impurities that are inevitably contained in the friction material are not contained. In addition, from the perspective of environmental load, the copper component mixed as an impurity is preferably 0.5% by mass or less.

[0025] The friction material of the present invention comprises a friction adjusting material, a fiber base material, and a binding material.

[0026] The friction adjusting material is used to impart the desired friction characteristics such as wear resistance, heat resistance, and fading resistance to the friction material. The inorganic particles having a Mohs hardness of 6 or more in the present invention function as grinding materials in the friction adjusting material, and the titanate functions as an inorganic filler in the friction adjusting material.

[0027] <Friction adjustment material: grinding material>

[0028] The grinding material is a component formulated for the purpose of grinding a disc rotor that serves as an object material and increasing the friction coefficient. The smaller the average particle size, the milder the grinding material. However, if it is too small, it is difficult to obtain the effect as a grinding material. In order to obtain the grinding effect, a large amount of grinding material must be used. In addition, the smaller the average particle size, the easier it is for the grinding material to enter the transfer film. If the grinding material enters the transfer film, the friction coefficient of the surface of the object material with the transfer film and the surface without the transfer film will easily differ. From this point of view, the friction material of the present invention does not contain inorganic particles (hereinafter, also recorded as inorganic particles (A)) with an average particle size of less than 3 μm and a Mohs hardness of more than 6.

[0029] Furthermore, the friction material of the present invention contains inorganic particles (hereinafter also referred to as inorganic particles (C)) having an average particle size of 15 μm to 60 μm and a Mohs hardness of 6 or more. By including inorganic particles of a large specific particle size as a grinding material, a transfer film is appropriately formed during braking, high wear characteristics are obtained, and impact resistance to the object material is appropriately imparted.

[0030] The average particle size of the inorganic particles (C) is preferably 17 to 50 μm, more preferably 20 to 40 μm.

[0031] The content of the inorganic particles (C) in the friction material is preferably 1 to 10% by mass, more preferably 2 to 8% by mass. When the content of the inorganic particles having a large particle size is within the above range, the thickness of the transfer film becomes sufficient.

[0032] As a grinding material, the friction material of the present invention preferably further contains: inorganic particles (hereinafter also referred to as inorganic particles (B)) having an average particle size of more than 3 μm and a Mohs hardness of more than 7. By using inorganic particles (C) having a large particle size and inorganic particles (B) having a medium particle size at the same time, it is possible to ensure both a moderate transfer film thickness and appropriate impact resistance to the target material.

[0033] The average particle size of the inorganic particles (B) is more preferably 3.5 μm to 10 μm.

[0034] The content of the inorganic particles (B) in the friction material is preferably 1 to 20% by mass, more preferably 5 to 15% by mass. When the content of the inorganic particles having a medium particle size is within the above range, the stability of the friction coefficient is improved.

[0035] In addition, from the viewpoint of wear resistance and formation of a stable transfer film, the content of the entire grinding material in the friction material is preferably 5% by mass to 30% by mass.

[0036] Examples of inorganic particles used as grinding materials include aluminum oxide (Mohs hardness: 9), silicon dioxide (Mohs hardness: 7), magnesium oxide (Mohs hardness: 6), zirconium oxide (Mohs hardness: 7), zirconium silicate (Mohs hardness: 7.5), chromium oxide (Mohs hardness: 6 to 7), iron tetroxide (Fe3O4) (Mohs hardness: 6), and chromite (Mohs hardness: 5.5). These can be used alone or in combination of two or more.

[0037] From the viewpoint of forming a transfer film on the surface of the target material, the inorganic particles (C) are preferably at least one selected from magnesium oxide, zirconium oxide, zirconium silicate, and ferrosoferric oxide (Fe 3 O 4 ).

[0038] From the viewpoint of increasing the friction coefficient, the inorganic particles (B) are preferably at least one selected from zirconium oxide and zirconium silicate.

[0039] The average particle size of the ground material is a value of a particle size (D50) corresponding to a cumulative percentage of 50% on a volume basis measured by a laser diffraction particle size distribution method.

[0040] <Friction Adjusting Material: Inorganic Filler>

[0041] (Titanate)

[0042] The friction material of the present invention contains a titanate (hereinafter also referred to as titanate (A)) having an average particle size of 20 μm or more. Titanate extends at the friction interface due to braking, which contributes to the formation of a transfer film. By containing a large-particle titanate having an average particle size of 20 μm or more, a transfer film is actively formed on the surface of the object material, thereby obtaining high wear characteristics. In addition, as titanate (A), by combining two or more types with different particle sizes, it is preferable to form a transfer film with a moderate thickness and a denseness. When two types of titanates with different particle sizes are used, the difference between the average particle sizes of the two is preferably 15 μm to 60 μm. In addition, from the viewpoint of making the thickness of the transfer film within a moderate range, the average particle size of the titanate is preferably 200 μm or less.

[0043] From the above viewpoints, the friction material of the present invention preferably contains titanate (A1) having an average particle size of 20 to 60 μm, and more preferably contains titanate (A2) having an average particle size of 40 to 160 μm in addition to titanate (A1).

[0044] The content of titanate (A) in the friction material is preferably 1% to 30% by mass. The inclusion of titanate (A) with a large particle size within the above range improves the stability of the friction coefficient and forms a sufficient transfer film based on the titanate, which is preferred. The content of titanate (A) is more preferably 5% to 25% by mass.

[0045] When the titanate (A1) and the titanate (A2) having different particle sizes are used in combination, the mixing ratio of the two is preferably 1:3 to 3:1 (mass ratio) from the viewpoint of forming a uniform transfer film.

[0046] It should be noted that the friction material of the present invention may contain titanate having an average particle size of less than 20 μm, but from the viewpoint of ensuring the friction coefficient, the content of titanate in the friction material is preferably 7% by mass or less.

[0047] The average particle size of the titanate is a value of a particle size (D50) corresponding to a cumulative percentage of 50% on a volume basis measured by a laser diffraction particle size distribution method.

[0048] As the particle shape of the titanate, it is preferably flaky (layered), columnar, plate-like, flat, needle-like, spherical, and amoeba-like, among which at least one of columnar and spherical is particularly preferred. By making the titanate columnar or spherical, it is easy to form a transfer film on the surface of the object material, so it is preferred. In addition, when using two or more titanates, from the viewpoint of uniformly forming a transfer film, it is more preferred to combine columnar and spherical shapes. In addition, columnar refers to a shape that is roughly columnar, such as a rod, a cylinder, a prism, a rectangle, a roughly cylindrical shape, a roughly rectangular shape, etc., which is distinguished from a needle-like shape. In addition, spherical refers to a roughly spherical shape such as a shape with concave-convex shapes on the surface and an elliptical cross-section, which is distinguished from a plate-like shape. In addition, the particle shape can be observed with a scanning electron microscope (SEM) or the like.

[0049] As the titanate, potassium titanate, lithium titanate, lithium potassium titanate, sodium titanate, calcium titanate, magnesium titanate, potassium magnesium titanate, etc. can be used. Among them, potassium titanate is particularly preferred from the viewpoint of improving the strength of the transfer film.

[0050] As the inorganic filler, in addition to titanate, an inorganic filler generally used in a friction material, such as barium sulfate, calcium carbonate, calcium hydroxide, vermiculite, and mica, may be contained.

[0051] The content of the inorganic filler in the friction material is preferably 20% by mass to 60% by mass, and more preferably 30% by mass to 50% by mass.

[0052] <Friction adjustment material: Other>

[0053] As the friction adjusting material, in addition to the grinding material and the inorganic filler, a friction adjusting material generally used in friction materials can be used, for example, an organic filler, a solid lubricant, a metal powder, etc. can be mentioned.

[0054] Examples of the organic filler include various rubber powders (raw rubber powder, tire powder, etc.), cashew nut powder, melamine dust, etc. These can be used alone or in combination of two or more.

[0055] The content of the organic filler in the friction material is preferably 1% by mass to 20% by mass, and more preferably 1% by mass to 10% by mass, based on the entire friction material.

[0056] Examples of the solid lubricant include graphite, phosphate-coated graphite, antimony trisulfide, molybdenum disulfide, tin sulfide, and fluorine-based polymers, etc. These may be used alone or in combination of two or more.

[0057] Phosphate coated graphite is graphite used as a solid lubricant coated with phosphate. By coating the graphite with phosphate, the transfer at high temperatures can be improved and the amount of wear can be reduced.

[0058] As the phosphate for coating graphite, the metal constituting the salt is preferably a metal belonging to the first group, the second group, the twelfth group or the thirteenth group of the periodic table (long period type). Specifically, it can be listed: Na and K belonging to the first group; Mg belonging to the second group; Zn belonging to the twelfth group; Al belonging to the thirteenth group; etc. Specifically, it is preferred to use at least one selected from the group consisting of aluminum phosphate, magnesium phosphate, calcium phosphate, potassium phosphate, sodium phosphate and zinc phosphate. From the viewpoint of water solubility, pH, etc., these phosphates are preferably hydrogen phosphates.

[0059] Regarding the method of coating graphite with phosphate, for example, a known method described in Japanese Patent Application Publication No. 2018-138652 can be used.

[0060] From the viewpoint of obtaining an appropriate transfer layer thickness, the content of the phosphate-coated graphite in the friction material is preferably 1% by mass to 10% by mass.

[0061] The content of the solid lubricant in the friction material is preferably 1% by mass to 25% by mass, and more preferably 3% by mass to 20% by mass.

[0062] Examples of the metal powder include powders of aluminum, tin, zinc, and the like, which can be used alone or in combination of two or more.

[0063] The content of the metal powder in the friction material is preferably 0.5% by mass to 10% by mass, and more preferably 1% by mass to 5% by mass.

[0064] <Fiber base material>

[0065] Fibrous substrates are used to reinforce friction materials.

[0066] As the fiber base material, various commonly used organic fibers, inorganic fibers, and metal fibers can be used, but it is preferred not to use copper fibers and bronze fibers containing a copper component.

[0067] Examples of the organic fiber include aromatic polyamide (aramid) fiber and flame-resistant acrylic fiber.

[0068] Examples of the inorganic fibers include ceramic fibers, biosoluble inorganic fibers, glass fibers, carbon fibers, and asbestos.

[0069] In addition, examples of metal fibers include steel fibers.

[0070] These fiber base materials can be used alone or in combination of two or more.

[0071] Here, for the friction material containing steel fiber as metal fiber, metal capture of the wear powder (metal component) of the counterpart material is likely to occur when the brake is applied, and thus it may become a cause of hindering the transfer of the friction material composition components to the surface of the counterpart material to form a transfer film. This is because the counterpart material is more easily ground due to the adhesive friction between the steel fiber and the cast iron as the counterpart material such as the disc rotor. In the friction material of the present invention, it is preferred that the metal fiber is not contained or used in a small amount, and the content of the metal fiber in the friction material is preferably less than 2% by mass.

[0072] In order to ensure sufficient mechanical strength, the content of the fiber base material in the friction material is preferably 1 to 20% by mass, more preferably 3 to 15% by mass, based on the total amount of the fiber base material.

[0073] <Bonding Materials>

[0074] The binder is formulated for the purpose of integrating the filler and the fiber base material etc. contained in the friction material composition to impart strength to the friction material.

[0075] As the binding material included in the friction material involved in the present invention, various commonly used binding materials can be used. Specifically, linear phenolic resins, various modified phenolic resins formed by elastomers, melamine resins, epoxy resins, polyimide resins and other thermosetting resins can be listed. Among them, from the viewpoint of imparting flexibility and waterproofness to the friction material, elastomer-modified phenolic resins are preferred. As elastomer-modified phenolic resins, acrylic rubber-modified phenolic resins, silicone rubber-modified phenolic resins, nitrile rubber (NBR)-modified phenolic resins, etc. can be cited. It should be noted that these binding materials can be used alone or in combination of two or more.

[0076] Furthermore, the content of the binder in the friction material is preferably 1% by mass to 20% by mass, and more preferably 3% by mass to 15% by mass, based on the entire friction material.

[0077] The specific method of manufacturing the friction material involved in the present invention can be carried out through a known manufacturing process. For example, the above-mentioned components can be prepared and the prepared product can be subjected to preforming, thermoforming, heating, grinding and other processes according to a common manufacturing method to produce the friction material.

[0078] The following is a general process for producing a brake pad including a friction material.

[0079] (a) A process of forming a press plate into a specified shape by sheet metal stamping;

[0080] (b) a step of degreasing, chemical conversion and primer treatment, and applying an adhesive to the press plate;

[0081] (c) preparing raw materials such as a fiber base material, a friction adjusting material and a bonding material, stirring them to fully homogenize them, and forming them at a predetermined pressure at room temperature to produce a preform;

[0082] (d) a hot forming step (forming temperature 130° C. to 180° C., forming pressure 30 MPa to 80 MPa, forming time 2 minutes to 10 minutes) of applying a predetermined temperature and pressure to the preform and a pressing plate coated with an adhesive to fix the two components integrally.

[0083] (e) Post-curing (150° C. to 300° C., 1 to 5 hours), followed by finishing treatments such as grinding, surface firing, and painting.

[0084] As described above, this specification discloses the following friction materials.

[0085] [1] A friction material comprising a friction adjusting material, a bonding material and a fiber base material, wherein:

[0086] The friction material does not contain inorganic particles with an average particle size of 3 μm or less and a Mohs hardness of 6 or more.

[0087] The friction material contains inorganic particles with an average particle size of 15 μm to 60 μm and a Mohs hardness of 6 or more.

[0088] The friction material contains titanate having an average particle size of 20 μm or more and does not contain a copper component.

[0089] [2] The friction material according to [1], wherein the titanate has a shape of at least one of a spherical shape and a columnar shape.

[0090] [3] The friction material according to [1] or [2], wherein the content of the titanate is 1% by mass to 30% by mass.

[0091] [4] The friction material according to any one of [1] to [3], wherein the friction material contains inorganic particles having an average particle size exceeding 3 μm and a Mohs hardness of 7 or more.

[0092] Example

[0093] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples.

[0094] (Example 1 to Example 12, Comparative Example 1 to Comparative Example 4)

[0095] The raw materials of the friction material formulation composition shown in Table 1 described below were mixed in a mixer for 5 minutes, and the mixed and stirred materials were put into a mold to perform pre-molding and heat-pressing molding to produce a friction material.

[0096] The preforming was performed by pressing at room temperature and a pressure of 5 MPa for 10 seconds.

[0097] The preform was heat-pressed at a pressure of 40 MPa and a molding temperature of 150° C. for 6 minutes to obtain a hot molded body.

[0098] The thermoformed body was post-cured at a temperature of 250° C. for 3 hours, and then processed, polished, and coated to a predetermined thickness to produce each friction material.

[0099] <Raw materials>

[0100] Potassium titanate (average particle size 40 μm, columnar): Otsuka Chemical Co., Ltd., TERRACESS JSL-R

[0101] Potassium titanate (average particle size 85 μm, spherical): Otsuka Chemical Co., Ltd., TERRACESSDP-R101

[0102] Potassium titanate (average particle size 7 μm, plate shape): Otsuka Chemical Co., Ltd., TERRACESS TF-S

[0103] Zirconia (average particle size 3.5 μm, Mohs hardness 7): Made by SAINT-GOBAIN ZIRPRO, CC10

[0104] Zirconium silicate (average particle size 1.1 μm, Mohs hardness 7.5): MZ-1000B manufactured by Daiichi Kizen Chemical Industry Co., Ltd.

[0105] Iron trioxide (average particle size 35 μm, Mohs hardness 6): manufactured by Pawdata Corporation, G1R348A

[0106] Iron oxide (average particle size 0.4 μm, Mohs hardness 6): TAROX synthetic iron oxide BL100 manufactured by Titanium Industry Co., Ltd.

[0107] Phosphate-coated graphite (aluminum phosphate treatment) is obtained by the following steps with reference to Japanese Patent Publication No. 2018-138652.

[0108] Aluminum dihydrogen phosphate was dissolved in pure water to prepare an aqueous solution with a concentration of 1% by mass. 42 parts by mass of artificial graphite (G-152A manufactured by Tokai Carbon Co., Ltd., with an average particle size of 700 μm) was added to 100 parts by mass of the aqueous solution, and stirred at a temperature of 50°C for 1 hour using a rotary blade mixer (PM-203 (model name) manufactured by Aswan Co., Ltd.). The obtained mixture was dried in the atmosphere for 24 hours and then crushed, and then heat-treated at 800°C for 3 hours in a vacuum. After the heat treatment, the mixture was crushed in a mortar to obtain a graphite powder (phosphate-coated graphite) whose particle surface was coated with aluminum dihydrogen phosphate.

[0109] <Evaluation Test of Friction Material>

[0110] The vibration characteristics of the friction materials of the examples and comparative examples prepared above were evaluated by measuring the torque fluctuation amount.

[0111] The test was conducted using a full-size dynamometer based on the AMS decay test. The torque fluctuation during 10 brakings in the AMS decay phase was measured, and the maximum value of the torque fluctuation was used for evaluation. The rotor vibration was set to 50±5μm.

[0112] The temperature at each location is measured using thermocouples driven into the rotor every 90 degrees.

[0113] Table 1 shows the evaluation results based on the following criteria.

[0114] Torque variation judgment criteria:

[0115] ◎: Less than 50N·m

[0116] ○: 50N·m or more and less than 80N·m

[0117] △: 80N·m or more and less than 100N·m

[0118] ×: 100 N·m or more

[0119] Temperature difference judgment criteria during 1 rotation:

[0120] ◎: Below 15℃

[0121] ○: 15℃ or above and below 20℃

[0122] △: 20℃ or above and below 30℃

[0123] ×: above 30℃

[0124] [Table 1]

[0125]

[0126] From the above results, it can be seen that for the friction materials of Examples 1 to 12, which do not contain zirconium silicate with an average particle size of 1.1μm and a Mohs hardness of 7.5 and iron oxide with an average particle size of 0.4μm and a Mohs hardness of 6, but contain iron oxide with an average particle size of 35μm and a Mohs hardness of 6 and potassium titanate with an average particle size of 40μm or 85μm, the torque variation and the temperature difference during one rotation of the rotor are at a level that does not cause any problem.

[0127] Among them, the friction materials of Examples 11 and 12 containing two kinds of potassium titanate having different average particle sizes and shapes showed particularly small torque fluctuations and temperature differences during one rotation of the rotor, which were good results.

[0128] For the friction materials of Comparative Examples 1 to 3 containing zirconium silicate with an average particle size of 1.1 μm and a Mohs hardness of 7.5 and ferrosoferric oxide with an average particle size of 0.4 μm and a Mohs hardness of 6 but not containing ferrosoferric oxide with an average particle size of 35 μm and a Mohs hardness of 6, and the friction material of Comparative Example 4 containing potassium titanate with an average particle size of 7 μm, the torque variation and the temperature difference during one rotation of the rotor both exceeded the reference values.

[0129] In particular, from the comparison between Example 3 and Comparative Example 3 in which the conditions of the grinding material are different, and from the comparison between Example 3 and Comparative Example 4 in which the conditions of potassium titanate are different, it can be seen that it is important to reduce the torque variation and reduce the temperature difference during one rotation of the rotor by not including a grinding material with a specific Mohs hardness and an average particle size, but including a grinding material with a specific Mohs hardness and an average particle size and containing potassium titanate with a specific average particle size.

[0130] The present invention is described in detail with reference to specific embodiments, but it is obvious to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on Japanese patent application (Japanese Patent Application No. 2022-109182) filed on July 6, 2022, the contents of which are incorporated herein by reference.

Claims

1. A friction material, characterized in that: It includes friction adjustment material, bonding material and fiber base material. The friction material does not contain inorganic particles with an average particle size of 3 μm or less and a Mohs hardness of 6 or more. The friction material contains inorganic particles with an average particle size of 15 μm to 60 μm and a Mohs hardness of 6 or more, and The friction material contains titanate having an average particle size of 20 μm or more and does not contain a copper component.

2. The friction material according to claim 1, characterized in that: The titanate particles have a shape of at least one of a spherical shape and a columnar shape.

3. The friction material according to claim 1 or 2, characterized in that: The content of the titanate is 1 mass % to 30 mass %.

4. The friction material according to claim 1 or 2, characterized in that: The friction material contains inorganic particles having an average particle size exceeding 3 μm and a Mohs hardness of 7 or more.

Citation Information

Patent Citations

  • Friction material

    JP2012197352A

  • Friction material composition, friction material and friction member using friction material composition

    JP2017002186A

  • Friction material

    JP2018138652A

  • Control system, movable body, control method and program

    JP2022109182A